Preliminary diagnostics of mathematical achievements of 4th class pupils - Balčiūnas, Sigitas; Kiseliova, Danutė; Kiseliovas, Arkadijus (Lietuvos matematikos rinkinys, 1998)
In the article is presented an information about experimental measurement of 4 the class pupils’ mathematical knowledge and skills. Also is given a methodological schedule of the test, test results interpretation in aspect of living place, predilection for mathematics, learning strategy of mathematics.